2017
DOI: 10.17051/ilkonline.2017.330249
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarının Çevre Bilinci ve Çevresel Duyarlılıklarının Çeşitli Değişkenler Açısından İncelenmesi

Abstract: ABSTRACT. This research examined the environmental awareness and environmental sensitivities of prospective teachers in terms of some variables. These are secondary education Biology, Physics, Chemistry, Sociology, Geography, History, and primary Science teachers. Obtaining the research data, the instrument developed by Yeşilyurt, Gül & Demir (2013) in order to assess prospective biology teachers' environmental awareness and sensitivity, was used in our study. Research was conducted using data gathered from 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
0
2
1
8
Order By: Relevance
“…The reason why the researcher had an expectation may be curiosity about the fact that the teacher whose branch is asked in the LGS exam might have a positive impact on students' preparation for the exam. However, the current study did not find a significant result so that the study was included in the literature which was not able to detect a significant difference on any educational variable for branch of teacher (Akçay & Pekel, 2017;Çam & Üstün, 2016;Şanlı, 2017).…”
Section: Discussioncontrasting
confidence: 58%
“…The reason why the researcher had an expectation may be curiosity about the fact that the teacher whose branch is asked in the LGS exam might have a positive impact on students' preparation for the exam. However, the current study did not find a significant result so that the study was included in the literature which was not able to detect a significant difference on any educational variable for branch of teacher (Akçay & Pekel, 2017;Çam & Üstün, 2016;Şanlı, 2017).…”
Section: Discussioncontrasting
confidence: 58%
“…Asunta (2004) reported that media and science teachers were the most important environmental sources and besides that the environmental behaviour and knowledge of girls were more positive than the boys. Besides of this, Akçay and Pekel ( 2017) had research with prospective teachers who were from different branches such as; biology, chemistry, physics, sociology, geography, history and primary science and established that gender in the branches and genders was not efficient factor through the environmental awareness and the environmental sensitivities. Similar with our study, Kuhlemeier et al (1999), reported that all relations between environmental behaviour, attitude and knowledge were substantial.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Bu süreçte ise öğrencilerin fen kavramlarını daha iyi anladığı, öğrenmeye karşı daha istekli ve ilgili olduğu, fene yönelik tutumlarına pozitif katkı sağladığı tespit edilmiştir (Topçu, Muğaloğlu ve Güven, 2014). Ancak hem karakter ve değerler boyutuna ilişkin araştırma sonuçları, hem de alan yazında ortaya çıkan diğer sonuçlar (Demirkaya, 2006;Boerwinkel, Knippels ve Warloo 2011;Topçu, Muğaloğlu ve Güven, 2014;Akçay ve Pekel, 2017 ) bireylerin sosyobilimsel konulara ilişkin karar verme becerilerini kullanmaya yeteri kadar yetkin olmadığı ve çevreye yönelik bilinçlerinde de eksiklikler olduğunu göstermiştir. Bu bakımdan literatürde elde edilen sonuçlar, gerek ekolojik dünya görüşü gerekse sosyobilimsel sorumluluk açısından araştırma sonuçlarıyla uyumlu olduğu görülmektedir.…”
Section: Tartışma Ve Sonuçunclassified